(untitled) (قضايا سياسية, 2024)
Summary: The events of the Al-Aqsa Tempest fall within the realm of complex and purposeful military operations, allowing the Palestinian resistance to strike deep into the Zionist entity. It exposed the entity's weaknesses and undermined the confidence of Israeli citizens in their authorities. The enormous impact of this operation on both the political and economic fronts continues to afflict the Zionist entity months after the event, with its repercussions potentially lingering for years. This necessitates a reevaluation of the aggressive policies it has long pursued.